2020
DOI: 10.1017/cem.2020.95
|View full text |Cite
|
Sign up to set email alerts
|

LO40: Safe anticoagulation initiation for atrial fibrillation in the emergency department (the SAFE pathway)

Abstract: Background: Atrial fibrillation (AF) is a risk for stroke. The Canadian Cardiovascular Society advises patients who are CHADS65 positive should be started on oral anticoagulation (OAC). Our local emergency department (ED) review showed that only 16% of CHADS65 positive patients were started on OAC and that 2% of our patients were diagnosed with stroke within 90 days. We implemented a new pathway for initiation of OAC in the ED (the SAFE pathway). Aim Statement: We report the effectiveness and safety of the SAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Arguably, the interventions most suitably aligned to a pharmacist"s skillset are those that focus on medication initiation, optimization and education. Pharmacist-led anticoagulant management services comprised of education, 18,20,27,28,33,36,37,44 adverse event monitoring 19,27,29,33,35,37,39,41,44 and dose-adjustment 18,20,37,44 were the most common interventions tested, as well as pharmacist identification of people with an atrial fibrillation diagnosis recorded with no evidence of anticoagulant prescription. 22,25,38,43,45 Overall, pharmacist interventions increased OAC prescription rates in eligible patients, and improved the appropriateness of prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Arguably, the interventions most suitably aligned to a pharmacist"s skillset are those that focus on medication initiation, optimization and education. Pharmacist-led anticoagulant management services comprised of education, 18,20,27,28,33,36,37,44 adverse event monitoring 19,27,29,33,35,37,39,41,44 and dose-adjustment 18,20,37,44 were the most common interventions tested, as well as pharmacist identification of people with an atrial fibrillation diagnosis recorded with no evidence of anticoagulant prescription. 22,25,38,43,45 Overall, pharmacist interventions increased OAC prescription rates in eligible patients, and improved the appropriateness of prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…32,38 Studies included patients on warfarin (n=9), 18-20, 23, 30, 36, 37, 39, 44 non-vitamin K antagonist oral anticoagulants (NOACs) (n=8) 17,27,[31][32][33][34][35]41 or both (n=1). 46 Nine studies referred broadly to anticoagulants, 22,24,25,28,29,38,40,43,45 and three evaluated antithrombotics. 21,26,42 Seven studies reported the quality of warfarin therapy, measured by time in therapeutic range (TTR), 18,20,30,36,37,39,44 seven reported on health outcomes (thromboembolism, bleeding, mortality), 19,27,29,33,35,39,44 15 reported on oral anticoagulant (OAC) prescribing, 21-26, 31, 34, 38, 40, 42, 43, 45, 46 28 one on patient knowledge 32 , one on patient cognition, 17 two on patient satisfaction 17,28 , and three on medication adherence.…”
Section: 'A' Anticoagulation/avoid Stroke: Pharmacist Interventions F...mentioning
confidence: 99%
See 2 more Smart Citations